Peningkatan Hasil Belajar Muatan IPA Peserta Didik pada Tema Peduli terhadap Makhluk Hidup Melalui Model Cooperative Learning Tipe CIRC di Kelas IV SDN 216/X Kuala Dendang Semester Ganjil Tahun Ajaran 2021/2022 - Murbiatun Murbiatun (Journal on Education, 2022)
This study aims to describe and obtain information on improving learning outcomes for the CIRC Type Cooperative Learning Model. This research is classroom action research which consists of two cycles, each cycle consists of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class IV SDN 216/X Kuala Dendang, totaling 8 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that through the CIRC Type Cooperative Learning Model, it could improve the learning outcomes of the fourth’s grade students of SDN 216/X Kuala Dendang science content by replacing group members.